Analisis Kemampuan Pemahaman Konsep Matematika Siswa Kelas XI MAS Al-Falah Klender Pada Materi Trigonometri - Choirunnisah Choirunnisah; Henardtin Henardtin; Iga Ayu; Nilam Dwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to analyze the understanding concepts of student to solve mathematical question in the trigonometry. The approach used in this research is a qualitative approache with the type of descriptive research. The population in this study were XI MIPA 1 MAS Al-Falah Klender Jakarta Timur in the 2023/2024 school year. The sample in this study was 20% off all state Madrasah Aliyah in Klender sub-district in Jakarta Timur which were selected by non-probability sampling technique with a type of purposive sampling. Data collection techniques used in this study by giving a test, the stages in this study are the stages of preparation, implementation, data analysis, preparation of research reports. The result of the research conducted at the Jakarta Timur Madrasah Aliyah can be concluded that the ability of class XI MIPA 1 MAS Al-Falah students to solve mathematical questions in the form trigonometry research 70,97%. That means the ability of students can be categorized as good.